2018
DOI: 10.1016/j.bpj.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Effects of the Proton Donor on the Microbial Proton Pump Proteorhodopsin

Abstract: Proteorhodopsin (PR) is a microbial proton pump that is ubiquitous in marine environments and may play an important role in the oceanic carbon cycle. Photoisomerization of the retinal chromophore in PR leads to a series of proton transfers between specific acidic amino acid residues and the Schiff base of retinal, culminating in a proton motive force to facilitate ATP synthesis. The proton donor in a similar retinal protein, bacteriorhodopsin, acts as a latch to allow the influx of bulk water. However, it is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…This specific position is documented to cause a ~20 nm bathochromic shift upon a glutamine (Q) to leucine (L) mutation. [13,15,[24][25][26][27][28][16][17][18][19][20][21][22][23] Experimental and computational studies have been performed to elucidate the exact nature of the Q105L color-tuning mechanism. [13,22,23,25,26,28,29] It was found that the color switching Q105L mutation affects the C 14 À C 15 bond length of the retinal polyene chain.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…This specific position is documented to cause a ~20 nm bathochromic shift upon a glutamine (Q) to leucine (L) mutation. [13,15,[24][25][26][27][28][16][17][18][19][20][21][22][23] Experimental and computational studies have been performed to elucidate the exact nature of the Q105L color-tuning mechanism. [13,22,23,25,26,28,29] It was found that the color switching Q105L mutation affects the C 14 À C 15 bond length of the retinal polyene chain.…”
Section: Introductionmentioning
confidence: 99%
“…[13,15,[24][25][26][27][28][16][17][18][19][20][21][22][23] Experimental and computational studies have been performed to elucidate the exact nature of the Q105L color-tuning mechanism. [13,22,23,25,26,28,29] It was found that the color switching Q105L mutation affects the C 14 À C 15 bond length of the retinal polyene chain. [21,22] In general, the bond length alternation (BLA) or bond order alternation (BOA), correlate strongly with the absorption maxima of rhodopsins.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations